Legal Challenges and Reform Proposals for Algorithmic Contracts under Indonesia’s Information and Electronic Transactions Law - Tejomurti, Kukuh; Sukarmi, Sukarmi; Mahmudy, Wayan Firdaus (Jambura Law Review, 2025)
The emergence of algorithmic contracts, made or carried out by independent systems, creates difficult legal problems, especially in Indonesia's regulatory environment. This study examines whether Indonesia’s Information and Electronic Transactions Law is adequate to deal with new problems with algorithmic pricing, EAs, and automated contract creation. The article also examines the different types of algorithmic contracts and how black-box algorithms are used in dynamic pricing in business competition. It shows how unclear the law is about agency, consent, and accountability.  Using doctrinal legal research combined with conceptual, comparative, and interdisciplinary approaches, the study finds that Indonesia's Information and Electronic Transactions Law and Competition Law have become inadequate in responding to developments in AI-driven transactions. It suggests a legal framework that does not favour any one technology and recognises algorithms as helpful agents. It also calls for changes to the law to clarify how electronic agents can work together and negotiate. This method ensures that businesses are held accountable and that the law is clear in the age of self-driving digital contracts.